Religious Internal Policy Integration Strategy: An Innovative Approach to the Protection of Workers’ Rights in Employment Agreements - Riswandie, Iwan; Syafa'i, Imam (Jurnal Pembaharuan Hukum, 2025)
Protecting workers' rights through internal policies that integrate religious values is a crucial innovative step in creating a fair, inclusive, and sustainable work environment in Indonesia. This study examines the strategy of integrating internal policies based on religious values as an innovative approach to protecting workers' rights in employment agreements. Using a mixed-methods explanatory sequential design, the study involved 15 multi-sector companies in Indonesia, along with 120 workers and 30 management/union representatives. Findings indicate that a strategy of multi-stakeholder collaboration and contextualizing abstract values into operational practices significantly increased job satisfaction (32%), procedural justice (41%), feelings of appreciation (38%), and employee retention (18%), while reducing stress symptoms (27%) and formal disputes (45%). The majority of workers (85%) supported the integration of universal, inclusive, and non-dogmatic religious values. The study also developed the RELIEF Evaluation Model (Religious Ethics-Led Impact Evaluation Framework) as a multidimensional framework for measuring the success of integration. The main contribution of this study is the provision of a tested collaborative implementation model, empirical evidence of holistic impact, and an innovative evaluation framework, which collectively enrich the literature on Ethical Human Resource Management and Employment Law.